The Effect of Thyroxine Treatment in Infertile Subclinical Hypothyroid Patients - Sudek, Hanan L. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Sub-clinical hypothyroidism (SCTD) is most commonly an early stage of hypothyroidism. Although the condition may resolve or remain unchanged, within a few years in some patients, overt hypothyroidism may develop, with low free T4 levels as well as a raised thyroid stimulating hormone(TSH) level. In general thyroid dysfunction is a condition known to reduce the likelihood of pregnancy and to adversely affect pregnancy outcome. As screening for thyroid disease becomes more common, SCTD is being diagnosed more frequently in clinical practice. The aim of the study is to find out the effect of treating SCTD with thyroxin on the fertility status of the female patient. Patients and methods: Forty three infertile patients attending the infertility clinic at Baghdad teaching hospital were compared to 32 control un explained infertility women. After exact history and examination, hormonal analysis (T3 and T4, TSH, Prolactin and Progesterone) and ultrasound were done for patients and control, then the patients were randomly divided into 2 groups one group was given thyroxine treatment, the other group was given parlodel, and after 3 months the hormonal analysis and ultrasound were repeated and compared to the previous results. Results: Comparing the patient group to the control showed a significant increase in the TSH and prolactin level in patients group but the progesterone concentration was not significantly different between the groups. After giving thyroxine the group who received it showed significant reduction in prolactin and improvement in the dominant follicle size and progesterone level while the group who was given parlodel showed only significant reduction in prolactin with no significant increase in the other 2 parameters. Conclusion: TSH in subclinical hypothyroidisim is correlated positively with age and with the prolactin concentration. Treatment with thyroxine induces a significant improvement in the fertility statues including the significant decrease in prolacttin concentration and increase in the dominant follicle size and increase in the progesterone level compared to those given parlodel only. This makes it obvious that treating patients with SCTD have a significant reflection on their fertility and ability for future pregnancy.